An Energy System Evaluation of Rural Electrification of Barangay Puray, Rodriguez, Rizal, Philippines - Olalo, Joselito (Archīum Ateneo, 2022)
Rural electrification in the Philippines is one of the main problems in the country. In this study, the possible electrification of Barangay Puray using three alternatives, namely, solar power, generator set and Meralco connection was analyzed. The stakeholders in this study were the people of the barangay, the local government of Rizal and the Meralco Corporation. Some assumptions are made, one of which is that the local government of Rizal will pay the capital costs for solar power and generator set, while the residents of the barangay will pay the government within 25-year period of the study. Here, two cases were introduced, whether the residents will pay the capital and maintenance costs or the maintenance costs only. The values of the initial costs and maintenance costs were compared and used to get the generation cost of the system. The results showed different values, with total of 189,889,720 pesos for the solar power while for the generator set was 235,425,304 pesos, thus the conclusion was made for the perspective of each of the stakeholder. For the residents of Barangay Puray, the most feasible was the solar power utility system. For the local government of Rizal, the generator set was more advantageous. While the Meralco Corporation would need the road laid out first before the electrification even it only has capital cost of 10,721,984 pesos in which the MOE was disregarded.